IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DI MTs. NEGERI MUARA ENIM - Muktasim Muktasim (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2015)
The education unit level curriculum is the operational curriculum to be implemented by the madrassa, in drafting the curriculum is delivered in educational institutions or madrassa. This study aims: to obtain a description of the implementation of the curriculum in MTs.N Muara Enim and o obtain a description of the supporting factors and obstacles for the implementation of the curriculum in MTs.N Muara Enim. The study measures used by the authors in this study is qualitative. Researchers started from one stage to the next. This type of research is the field of survey research methods. Data collection techniques are observation, documentation and interview. Notch researchers in qualitative research than as planners as well as implementing a data collection or as an instrument.